Translating into Textual Genres - García Izquierdo, Isabel; Montalt i Resurrecció, Vicent (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
When we translate, we do so for specific communicative situations and purposes; that is, we write translations that will fulfil the needs and conventions of specific textual genres in the target language and culture. The aim of this article, which draws on data and experience from the GENTT project, is to explore the relationship between translation and genre theory in order to understand better how translators are involved in interlinguistic and intercultural communication. Genre theory is attractive to Translation Studies because it links the micro level of writing and text to the macro level of discourse and context, unites process with product and integrates the cognitive, social and profes¬sional approaches to translation. Thus, the notion of genre brings together critical elements in translation such as the reader ’s profile, expectations and preferences; the communicative situation and purpose; and the socio-cultural context. In order to understand better how translators are involved in interlinguistic and intercultural communication, we suggest a remodelling of translation in which the target genre plays a central role.